Hygrothermal aging effects on flexural behavior of pultruded glass fiber reinforced polymer laminates in bridge applications. (30th November 2016) - Xin, Haohui; Liu, Yuqing; Mosallam, Ayman; Zhang, Youyou; Wang, Congzhe
Highlights: Flexural tests of pultruded GFRP laminates exposed to six different hygrothermal aging environments were conducted. The long-term hygrothermal aging effects on flexural properties accounting for temperature variation during exposure were predicted by combining Phillips equation and Arrhenius relationship. Predicted results were compared with design values prescribed by ACI-440, TR-55 and GB50608 design guidelines. Abstract: It is significant for designers to consider not only short-term characteristics but also the long-term properties of composite materials that are commonly used in highway bridge applications. In this study, flexural tests were performed on composite specimens that were exposed to both fresh water and artificial seawater environments at 40 °C, 60 °C and 80 °C temperatures. The purpose of conducting these tests is to (1) investigate the hygrothermal aging effects on flexural properties of pultruded fiber reinforced polymer (PFRP) composites, and (2) to establish relationship between flexural strength and flexural modulus and hygrothermal aging time. Based on the results of this study, it was found that: (i) the degradation in both average flexural strength and modulus increases at higher temperatures; (ii) the degradation in transverse flexural strength and modulus is relatively higher as compared to those observed for longitudinal flexural strength and modulus; and (iii) the reduction in average flexural strength and modulus for specimens exposed to fresh water and artificial seawater environments is relatively small. The long-term hygrothermal aging effects on flexural properties of PFRP laminates, including temperature variation during exposure, were predicted using both Phillips equation and Arrhenius relationship. The predicted flexural strength, flexural modulus and coefficient " A " agreed well with experimental results. The hygrothermal aging effects on flexural properties, at room temperature (23 °C) after 100.0 years, were predicted and compared with design values prescribed by ACI-440, TR-55 and GB50608 design guidelines provisions. Results of this study confirmed the reliability of design values recommended by ACI-440 design guidelines that were found to be similar to experimental results, while design values produced by following procedures recommended by both TR-55 and GB 50608 documents are about 1.75–2.25 times larger than the predicted values.